Analysis of background factors in marine accidents and incidents caused by watch-keeper drowsiness in Japan - Shinsuke Urushidani; Toshiki Kikuchi; Toshikazu Terasawa; Yuji Sano (Актуальні проблеми транспортної медицини, 2011)
The purpose of this study was to perform a feature extraction of sleep and lifecycle characteristics among watch-keepers involved in marine accidents and incidents. A questionnaire that included attributes of the watch-keeper, amount of sleep, problems related to sleep, fatigue, feeling hiyari-hatto incidents, and the Epworth sleepiness scale (ESS) was administered to a sample of 7,750 watch-keepers (response rate - 21.3%). Watch:keepers have problems related to sleep, such as “once a month or more awaking while sleeping and cannot sleep afterwards”, “once a month or more awaking too early in the morning and cannot sleep afterwards”, “I have been told by my family and colleagues that I snore”, and “I had my breathing stopped while sleeping”. Some watchkeepers indicated “once a month or more feeling hiyari-hatto incidents” The analysis of cargo ships and tankers revealed there was a notable relationship between the situation of “once a month or more feeling hiyari-hatto incidents” and the influence of each “frequency of interrupted sleep”, “sleep delay”, “frequency of interrupted sleep” and ”early morning sleeplessness”. These results suggest that watch-keeper of each ship have problems related to sleep due to sleep and lifecycle characteristics.